A case study on difficulties experienced by school children with dyslexia in Kelantan - Siti Wan Aminah Wan Norudin (2019)
The purpose of this qualitative case study is to explore difficulties experienced by school children with dyslexia in literacy, numeracy, phonological processing, and in left-right orientation. The difficulties faced by children with dyslexia in this study were explored based on the Bangor Dyslexia Test (BDT) together with several other tasks. This study involved five school children diagnosed with dyslexia by medical practitioners. The school children were from three different primary schools and were enrolled in a dyslexia special education programme. Data was collected through multiple techniques including interviews, documents analysis, and non-participant observations. The findings indicate that all participants displayed difficulties in literacy, numeracy, phonological processing, and in left-right orientation. Findings show that the participants have difficulties in terms of letter reversals, inaccuracy in naming the letters of the alphabet, inaccuracy in articulating spelt words, and also difficulties in spelling. In terms of numeracy, findings reveals that the participants have difficulty in carrying out oral calculations, hesitating in answering questions, refusing to answer questions completely, and also difficulties in reciting the times tables correctly. With regards to phonological processing tasks, findings show that the participants hesitated and refused to answer naming speed tasks, had low digit span ability and responded incorrectly to the phonological elision task. Similarly, the participants hesitated and were confused over the left- right coordination, especially when it involved other people’s body parts. Nevertheless, findings of the present study add knowledge to literature in exploring difficulties experienced by school children with dyslexia, specifically in literacy, numeracy, phonological processing, and in left-right orientation, in the Malaysian context.